HÀM LƯỢNG 20-HYDROXYECDYSONE TRONG MỘT SỐ LOÀI THỰC VẬT VƯỜN QUỐC GIA NAM CÁT TIÊN - Vũ, Thị Loan; V.V, Volodin; S.O., Volodina; Phạm, Khắc Linh; Nguyễn, Thị Vân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE CONTENTS OF 20-HYDROXYECDYSONE IN SOME PLANTS OF THE NAM CAT TIEN NATIONAL PARK Phytoecdysteroids are secondary metabolites which were found in many plant species. In mammals, including humans, phytoecdysteroids don’t have hormonal activity, low toxicity and are proven to have many pharmacological effects. 20-hydroxyecdysone (20E) is one of the most common phytoecdysteroids which was detected in plants. In this study, 20E was detected in some plants of Vitex and Sida genera of the Nam Cat Tien national park. HPLC method was used for determining 20E. 3,44% was the highest concentration of 20E picked out from young Vitex tripinnata leaves. Vitex canescens and Vitex tripinnata were considered as potential plants for producing ecdysteroid-containing drugs.